2006
DOI: 10.1021/ol061274f
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-Based Switch-On Molecular Sensor for Cu(II) in Buffer:  Absorption and Fluorescence Study of the Selective Recognition of Cu(II) Ions by Galactosyl Derivatives in HEPES Buffer

Abstract: [graph: see text] 1-(Beta-D-galactopyranosyl-1'-deoxy-1'-iminomethyl)-2-hydroxynaphthalene (L1), possessing an ONO binding core, was found to be selective for Cu2+ ions in N-[2-hydroxyethyl]piperazine-N'-[2-ethanesulfonic acid] buffer, at concentrations < or = 580 ppb, at physiological pH by eliciting switch-on behavior, whereas the other ions, viz., Mg2+, Ca2+, Mn2+, Fe2+, Co2+, Ni2+, Zn2+, and Cd2+, caused no significant change in the fluorescence. Whereas the binding characteristics were ascertained by abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…-sensitive probes that are not soluble in water. [122][123][124][125][126][127] The detection limit of this probe is 0.2 μM, and we have shown that the fluorimetric detection of Cu , not even when these ions are present in large excess (100 molar equiv.). Although these features may appear promising for fluorimetric detection of Cu 2+ ion with chemosensor 10, this probe is far from being ideal, because it does not exhibit the anticipated shift of the emission maximum on metal-ion binding.…”
Section: Cation-sensitive Fluorescent Probesmentioning
confidence: 86%
See 1 more Smart Citation
“…-sensitive probes that are not soluble in water. [122][123][124][125][126][127] The detection limit of this probe is 0.2 μM, and we have shown that the fluorimetric detection of Cu , not even when these ions are present in large excess (100 molar equiv.). Although these features may appear promising for fluorimetric detection of Cu 2+ ion with chemosensor 10, this probe is far from being ideal, because it does not exhibit the anticipated shift of the emission maximum on metal-ion binding.…”
Section: Cation-sensitive Fluorescent Probesmentioning
confidence: 86%
“…128 To overcome the above mentioned shortcomings of probe 10 we turned our attention to crown-ether functionalities as receptor units, because it has been demonstrated already with numerous examples that the direct attachment of azacrown ether units to a fluorophore is a general design principle for the development of donor-acceptor based fluorescent probes that change emission wavelength upon complexation of a metal ion (Scheme 1c). [3][4][5][6][7][8][9][10][11][12][122][123][124][125][126][127] Nevertheless, most crown ether host molecules do not bind the analyte to significant extent in water, 129 so that the majority of probes can only operate in non-competitive organic solvents. Therefore, we focused our studies on the 1,4-dioxa-7,13-dithia-10-azacyclopentadecane receptor unit, that is known to bind Hg 2+ ions in water with high affinity.…”
Section: Cation-sensitive Fluorescent Probesmentioning
confidence: 99%
“…Similarly in case of fluorescence emission spectral recording, there was sharp decrease in the emission signal at 496 nm up to 5 μM Cu 2+ addition when it was excited at 328 nm. 19 Chemical structure of the receptor 22 and proposed ligand-metal complexation mechanism Singhal et al 100 described the synthesis and copper binding affinity of the ligands 23 ( Fig. With further increase in the copper ion concentration up to 10 μM, a large red shift was observed from 496 to 616 nm with the isoemissive point at 550 nm attributed to the host-guest complex formation via coordination of the free pyrrolidinium nitrogen with Cu 2+ .…”
Section: Naphthalene Based Cu 2+ Sensormentioning
confidence: 99%
“…Hence a gluco-based molecular receptor has been designed and synthesized and was explored as a new fluorescent probe for Cu 2+ . Though there are a few glyco-based receptors reported in the literature for Cu 2+ sensing, these were not shown for their suitability to use in blood serum milieu or any other biologically relevant medium [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%